EFFECT OF NUTMEG CONCENTRATION IN NUTMEG JAM AND CAKES ON ACCEPTABILITY, NUTRITIONAL CONTENT AND ANTIOXIDANT ACTIVITY - Endang Rumayomi; Briliannita, Anjar; Fajar Irianto (Universitas Airlangga, 2025)
Nutmeg, a key agricultural product of Fak-Fak Regency, is processed into diverse food products, including jams utilized in mini lontar cakes and rolled tart cakes. This study aimed to optimize the use of nutmeg flesh in jam production, evaluating its nutritional composition, antioxidant properties, and consumer acceptability. Conducted as an experimental study employing a completely randomized design (CRD), six formulations of nutmeg jam (S0 to S5) were prepared and analyzed. A sensory evaluation was performed by 30 semi-trained panelists from the Nutrition Department of the Polytechnic of the Ministry of Health, Sorong. Statistical differences in acceptability were assessed using the Kruskal-Wallis and Mann-Whitney U tests (α ≤ 0.05). The results identified S5 (50% nutmeg pulp and 50% sugar) as the most preferred formulation, with significant differences in taste (p = 0.01) and texture (p = 0.03), but no notable differences in color (p = 0.06), aroma (p = 0.33), or overall acceptance (p = 0.99). Nutritional analysis revealed a carbohydrate content of 45.09% and antioxidant activity of 69.8%, comparable to raw nutmeg pulp (70.4%). Furthermore, mini lontar cakes and rolled tarts incorporating S5 jam demonstrated superior carbohydrate levels (53.92% and 38.09%, respectively) and antioxidant activities (35.8% and 41.5%). These findings underscore the potential of nutmeg-derived products in contributing to functional food development, supporting the diversification of nutmeg-based snacks as a source of bioactive compounds and nutritional benefits.